Volume 4: Heat Transfer, Parts a and B 2012
DOI: 10.1115/gt2012-68863
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Combustor Effusion Cooling Under Conditions of Very High Free-Stream Turbulence

Abstract: Full-coverage or effusion cooling is commonly used in the thermal management of gas turbine combustion systems. The combustor environment is characterised by highly turbulent freestream flow conditions and relatively large turbulent length scales (length scale-to-coolant hole diameter ratios in excess of 30) that are primarily created by the fuel injector and dilution jets; indeed, the available evidence suggests that large energetic eddies interact strongly with the coolant flows and may have a significant im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
3
7
0
Order By: Relevance
“…A reduction of film coverage is observed when turbulence increases, but the impact is largely reduced with blowing ratios approaching 1.0. More recently Martin and Thorpe [14] observed an increase of adiabatic effectiveness with realistic high free stream turbulence when using inclined holes at blowing ratio above 1.0: this is due to an increased mixing rate of the jet with the mainstream, which enhance the amount of coolant close to wall region. The investigation carried out by Scrittore et al [15] was focused on the measurement of adiabatic film effectiveness and flow field from inclined effusion cooling jets in a range of blowing ratios (3.2 to 5.0) that can be observed in actual combustors.…”
Section: Introductionmentioning
confidence: 97%
“…A reduction of film coverage is observed when turbulence increases, but the impact is largely reduced with blowing ratios approaching 1.0. More recently Martin and Thorpe [14] observed an increase of adiabatic effectiveness with realistic high free stream turbulence when using inclined holes at blowing ratio above 1.0: this is due to an increased mixing rate of the jet with the mainstream, which enhance the amount of coolant close to wall region. The investigation carried out by Scrittore et al [15] was focused on the measurement of adiabatic film effectiveness and flow field from inclined effusion cooling jets in a range of blowing ratios (3.2 to 5.0) that can be observed in actual combustors.…”
Section: Introductionmentioning
confidence: 97%
“…The development of a combustor-style turbulence generator for cascade testing was first reported by Ames and Moffat [5]. A number of studies have since investigated the impact of combustor turbulence on downstream components [6][7][8][9][10][11][12][13]. These studies have mainly focused on the effect of combustor turbulence on wall shear stress and heat transfer on a flat plate.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion that high freestream turbulence decreased the overall effectiveness is contradictory to previous studies that look at adiabatic effectiveness of effusion liners. As mentioned before, Martin and Thorpe [3] and Kakade et al [4] found that high freestream turbulence, compared to low freestream turbulence, resulted in a higher adiabatic effectiveness for effusion blowing ratios in the range of M eff,in ¼ 0.5-1.5. The reason given by each author for the increased effectiveness was that when there was jet lift off, the turbulent mixing brought some of the coolant back to the surface.…”
Section: Resultsmentioning
confidence: 71%
“…In a different study with only effusion cooling, Facchini et al [2] found that increasing the effusion blowing ratio generally led to decreased adiabatic effectiveness due to jet separation; however, overall effectiveness increased at high blowing ratios due to in-hole convection. Martin and Thorpe [3] studied the effects of freestream turbulence intensity on effusion cooling without dilution jets and found that at low blowing ratios of the effusion jets (M eff,in < 0.5), high freestream turbulence resulted in decreased adiabatic effectiveness; whereas at relatively high blowing ratios, up to M eff,in ¼ 1.4, high freestream turbulence caused an increase in adiabatic effectiveness. This phenomenon was attributed to the turbulent mixing that brought separated coolant back toward the surface.…”
Section: Relevant Past Studiesmentioning
confidence: 99%